Educational Transformation in The Digital Era - Yanuarini, Dwi; Masykur, Masykur (PPSDP International Journal of Education, 2024)
This research uses a literature study approach which aims to determine the quality of learning at SMA Negeri 1 Payaraman through the transformation of education in the Era of digital development. The method used in this study is a literature review of several previous studies using data collection techniques, reading and recording and processing research materials then a review is carried out. The review process carried out at SMA Negeri 1 Payaraman has improved the quality of learning through educational transformation including increased learning, increased knowledge, no distance, easier evaluation of learning outcomes, increased learning outcomes, the realization of a collaborative learning atmosphere, and made it easier for teachers and homeroom teachers to manage grades and write report cards. However, behind the advantages, there are disadvantages of the transformation of digital era education, including technology making students less productive and lazy, high cheating rates, less focus and decreased interest in learning, and decreased writing skills.